1992
DOI: 10.1080/01688639208402858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of severe closed-head injury on three stages of information processing

Abstract: The present study investigated the loci of the information-processing delay that characteristically follows severe closed-head injury (CHI). Sternberg's additive-factors logic was used to determine the effects of severe CHI on the central information-processing stages of stimulus encoding, memory comparison, and decision-making/response-selection. The task variables used to define the stages operationally were stimulus quality, memory set size, and stimulus-response compatibility. Twenty subjects who had susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 31 publications
4
56
0
Order By: Relevance
“…Thus, interference was high at the level of response sets, and this might explain the greater switch costs for the CHI group in this study. Consistent with this possibility, previous studies in the CHI literature have repeatedly demonstrated inefficiencies in the response selection stage of information processing following severe CHI (e.g., Schmitter-Edgecombe, Marks, Fahy, & Long, 1992;Shum, McFarland, Bain, & Humphreys, 1990;van Zomeren, 1981).…”
Section: Discussionmentioning
confidence: 57%
“…Thus, interference was high at the level of response sets, and this might explain the greater switch costs for the CHI group in this study. Consistent with this possibility, previous studies in the CHI literature have repeatedly demonstrated inefficiencies in the response selection stage of information processing following severe CHI (e.g., Schmitter-Edgecombe, Marks, Fahy, & Long, 1992;Shum, McFarland, Bain, & Humphreys, 1990;van Zomeren, 1981).…”
Section: Discussionmentioning
confidence: 57%
“…Some previous studies have concluded that the response selection stage is slowed in CHI on the basis of larger effects of differences in S-R compatibility in CHI compared to controls (Shum et al, 1990;Schmitter-Edgecombe et al, 1992), although there are contradictory findings (Stokx and Gaillard, 1986). The lack of such differential effects here perhaps can be best attributed to a very weak overall compatibility effect: There were no main effects of S-R mapping for all the conditions or in the analyses of the simple effects for the Choice and SD conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Greater effects of S-R compatibility in CHI have been reported (Shum et al, 1990;Schmitter-Edgecombe, Marks, Fahey, & Long, 1992), even in one group without significantly elevated overall RT (Shum et al, 1990). However, Stokx and Gaillard (1986) had previously failed to find a differential effect of S-R compatibility in a brain injured group despite slower RT overall in patients than in controls.…”
Section: Experiments 3 Choice Rt and Sen-sory Dominancementioning
confidence: 94%
“…From a cognitive point of view, there is still a lack of consensus as to which of the specific stages are impaired in TBI. Some authors have postulated a slowed stimulus identification, while others have proposed that the response selection is the principal stage that is impaired in this population [28,62,63].…”
mentioning
confidence: 99%